Retinal vascular fractal dimension and cerebral blood flow, a pilot study. Issue 1 (23rd September 2019) - Nadal, Jeremy; Deverdun, Jeremy; de Champfleur, Nicolas Menjot; Carriere, Isabelle; Creuzot‐Garcher, Catherine; Delcourt, Cécile; Chiquet, Christophe; Kawasaki, Ryo; Villain, Max; Ritchie, Karen; Le Bars, Emmanuelle; Daien, Vincent
Abstract: Purpose: Ocular and brain microcirculation share embryological and histological similarities. The retinal vascular fractal dimension (FD) is a marker of retinal vascular complexity of the vascular tree. The purpose of this study was to explore the relationship between cerebral blood flow (CBF), retinal vascular FD and other retinal vascular markers. Methods: Cross‐sectional analysis comprising 26 individuals ≥65 years old from the Cognitive REServe and Clinical ENDOphenotype (CRESCENDO) cohort of relative healthy older adults. Retinal vascular FD was measured from fundus photographs by using the semi‐automated Singapore Eye Vessel Assessment (SIVA) software. CBF was estimated using a 2D pulsed ASL MRI sequence. Associations between blood flow and retinal parameters were analysed using linear regression models adjusted for age and sex. Results: Cerebral blood flow was positively associated with venular FD ( R 2 = 0.32, p = 0.03). This association was stronger in the anterior versus posterior brain territories ( R 2 = 0.35 [p = 0.001] versus R 2 = 0.16 [p = 0.07], respectively). Global CBF was correlated with arteriolar branching angle ( R 2 = 0.23, p = 0.01) and tortuosity ( R 2 = 0.20, p = 0.02). Global CBF was not correlated with other SIVA parameters. Conclusions: Retinal venular complexity summarized by the FD was associated with cerebral blood flow as well as retinal arteriolar tortuosity and branching angle. Larger prospective clinical studies are needed to confirm these results.